The Role of Viral and Host miRNAs in The Control, Progression and Possible Treatment of Covid-19 Disease - Alireza Monadi Sefidan; Reza Afrisham (Tehran University of Medical Sciences, 2022)
Background and Aim: Previous studies have shown that viral and host miRNAs play a role in the process of controlling or progressing the disease and can even be considered as therapeutic targets. Accordingly, the present review study was designed to evaluate the role of host miRNAs and Covid-19 virus in the disease process.  Materials and Methods: The current study was a review study that was conducted during 2012-2022. Studies were extracted from PubMed, Google Scholar, Web of Science and Scopus scientific databases. The researchers selected relevant resources and a summary of them was presented in this review. Results: The present review study showed that some host miRNAs such as miR-23b-5p, miR-200c, and miR-125a-5p had an inhibitory effect on ACE2 receptor, while miR-3909, miR-4677, and miR-133a had a stimulatory effect on this receptor. Furthermore, host miR-98-5p had an inhibitory effect on TMPRSS2 gene expression. On the other hand, host miR-146a, miR-21, and miR-142 induced inflammation through MAPK and NF-Ƙβ signaling. While, host miR-124, miR-410, and miR-1336 inhibited factor STAT3 and prevented inflammation. Furthermore, host miR-302b and miR-372 targeted the mitochondrial antiviral signaling protein (MAVS), resulting in silencing of type 1 interferon signaling. It has also been established that host exosomal miR-7-5p, miR-24-3p, miR-145-5p, and miR-223-3p inhibited the replication of SARS-CoV-2 and the expression of S protein and their decreased expression in elderly and Diabetic subjects was associated with decreased inhibition of SARS-CoV-2 replication. Moreover, viral miR-359-5p regulated the expression of MYH9 (non-muscle myosin heavy chain 9), which caused virus invasion and release in the host cell. Conclusion: This study showed that many miRNAs play a role in controlling or progressing the disease of Covid-19 and it is possible to treat the disease of Covid-19 by changing the expression of viral and host miRNA. However, more research is needed in this regard.